A Descriptive-Quantitative Analysis of Natural Resource Sub-Sectors and Their Impact on Regional Development Performance in Central Bangka Regency, Indonesia - Ratih Kusumastuti; Septi Angraeni (Equity: Jurnal Ekonomi, 2023)
Central Bangka Regency is part of the Bangka Belitung Islands Province which is an integral part of the Unitary State of the Republic of Indonesia whose formation was based on Law Number 5 of 2003 concerning the Formation of South Bangka Regency, Central Bangka Regency, West Bangka Regency and East Belitung Regency in the Archipelago Province. Bangka Belitung. The purpose of the evaluation is to assist regional development planning documents, to identify potential natural resources sub-sectors in Central Bangka Regency related to regional development performance achievement indicators. The study approach used in this activity is descriptive-quantitative. Based on Location Quotient (LQ) analysis, there are 8 potential economic sectors or comparative advantage (base). There are 4 sectors that do not have a comparative advantage (non-base) or local and there are 3 sectors that are not potential (non-basic). Middle. In the second quadrant, there are commodities that have a slow growth rate but a large contribution to the GRDP of Central Bangka Regency. In the third quadrant, there are commodities that have a fast growth rate but a small contribution to the GRDP of Central Bangka Regency. In the fourth quadrant, there are commodities that have a slow growth rate and make a small contribution to the GRDP of Central Bangka Regency